Meningkatkan Kemandirian Belajar PPKn melalui Penerapan Model Self Directed Learning (SDL) di SMPN 6 Garut - Tetep; Anjani, Dewi Mega; Indah, Dhebby; Adelin, Fitra Surya; Mulyani, Sri Sugeng (PTK: Jurnal Tindakan Kelas, 2025)
Issues surrounding students’ learning independence often stem from the prevalent use of conventional teaching methods by educators. This research seeks to explore the effectiveness of the Self-Directed Learning (SDL) model in fostering greater independence among students in PPKN (Civics) learning. The study employs a classroom action research approach, utilizing Kurt Lewin’s revised cycle model, which includes four phases: (1) planning, (2) implementation, (3) observation, and (4) reflection. The research sample was selected through purposive sampling, focusing on class VIII-A as the subject of the study. Data collection was conducted using tests, observations, and documentation. The data analysis involved descriptive percentage techniques specific to PPKN learning outcomes. Findings from the hypothesis testing revealed that the SDL model significantly contributed to enhancing students' independence in learning PPKN. This is evidenced by continuous improvement across each cycle, culminating in a final average percentage of 74.98% by the third cycle—meeting the expected criteria. Thus, it can be concluded that the Self-Directed Learning (SDL) model effectively promotes learning independence in PPKN subjects.